Comparative transcriptomics across 14 Drosophila species reveals signatures of longevity. Issue 4 (19th April 2018) - Ma, Siming; Avanesov, Andrei S.; Porter, Emily; Lee, Byung Cheon; Mariotti, Marco; Zemskaya, Nadezhda; Guigo, Roderic; Moskalev, Alexey A.; Gladyshev, Vadim N.
Summary: Lifespan varies dramatically among species, but the biological basis is not well understood. Previous studies in model organisms revealed the importance of nutrient sensing, mTOR, NAD/sirtuins, and insulin/IGF1 signaling in lifespan control. By studying life‐history traits and transcriptomes of 14 Drosophila species differing more than sixfold in lifespan, we explored expression divergence and identified genes and processes that correlate with longevity. These longevity signatures suggested that longer‐lived flies upregulate fatty acid metabolism, downregulate neuronal system development and activin signaling, and alter dynamics of RNA splicing. Interestingly, these gene expression patterns resembled those of flies under dietary restriction and several other lifespan‐extending interventions, although on the individual gene level, there was no significant overlap with genes previously reported to have lifespan‐extension effects. We experimentally tested the lifespan regulation potential of several candidate genes and found no consistent effects, suggesting that individual genes generally do not explain the observed longevity patterns. Instead, it appears that lifespan regulation across species is modulated by complex relationships at the system level represented by global gene expression.